Optimal Allocation of Distributed Generation and Distribution Static Compensator Using Improved Multi-Objective Function and INFO Optimization Algorithm - Abdollahi, Rohollah; Abdolhosseini, Morteza (Jordan Journal of Electrical Engineering, 2025)
This paper presents an improved multi-objective function (MOF) by simultaneously applying the voltage stability index (VSI) and system loadability (SL) for sustainable operation of a distribution network via the optimum location and sizing of distributed generations (DGs) and distribution static compensators (DSTATCOMs). In other words, with the approach of increasing the voltage profile, first, the candidate busbar for installation is determined based on the VSI, and then, by applying higher weights in the mentioned function, more priority is given to these busbars. This function is optimized by weighting candidate busbars using the INFO algorithm. The system loadability is included in the multi-objective function along with the total costs (involving the investment costs of distribution static compensators and distributed generations) and network loss. The sizes of the DGs and DSTATCOMs are enhanced using an INFO optimization algorithm. The operational economic benefits are represented by calculating the annual cost savings. The effectiveness of the proposed methodology is evaluated on 33- and 69-node distribution networks. Based on the findings, the proposed methodology is found to be more effective compared to other methods reported in the literature, and it provides more optimal answers compared to the non-consideration of the VSI.